2002
DOI: 10.2133/dmpk.17.357
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of the N-acetyltransferase2 Polymorphism in the Prediction of Adverse Drug Reactions to Isoniazid in Japanese Patients

Abstract: To investigate the association between NAT2 genotypes and the incidence of isoniazid (INH)-induced adverse reactions, in the hope of identifying a pharmacogenetic approach that could be useful in the prediction and prevention of adverse reactions in Japanese patients, we retrospectively studied the genotypes of NAT2 in 102 Japanese patients treated with INH (without rifampicin co-administration). The subjects were classified into three groups according to their genotypes: rapid-type, intermediate-type, and slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
4
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 16 publications
5
39
4
2
Order By: Relevance
“…The proportion of rapid acetylator was also dominant in China (71-80%) and Japan (91-94%). 4,5,9,10,11 Contrary to our result, the slow acetylator was dominant in several populations. The proportion of slow acetylator was slightly higher than rapid acetylator on studied conducted in India (55%) and Brazil (55%).…”
Section: Figurecontrasting
confidence: 99%
See 3 more Smart Citations
“…The proportion of rapid acetylator was also dominant in China (71-80%) and Japan (91-94%). 4,5,9,10,11 Contrary to our result, the slow acetylator was dominant in several populations. The proportion of slow acetylator was slightly higher than rapid acetylator on studied conducted in India (55%) and Brazil (55%).…”
Section: Figurecontrasting
confidence: 99%
“…This included several studies conducted in China, Japan, India, and Brazil. 3,5,6,9,10,11,12 This study showed the major acetylator status in tuberculosis patients were rapid acetylator. This indicated that the risk of hepatotoxic effect after tuberculosis treatment in most of our subjects was relatively not high.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Despite the dosage of the drug used for chemotherapy of TB, different drug-related adverse reactions have been observed, including peripheral neuritis, fever, visual damage, gastric intolerance, nettle rash and hepatic toxicity (1,2).…”
Section: Introductionmentioning
confidence: 99%